Identification of new dystroglycan complexes in skeletal muscle. - Eric K Johnson; Bin Li; Jung Hae Yoon; Kevin M Flanigan; Paul T Martin; James Ervasti; Federica Montanaro (PLoS ONE, 2013)
The dystroglycan complex contains the transmembrane protein β-dystroglycan and its interacting extracellular mucin-like protein α-dystroglycan. In skeletal muscle fibers, the dystroglycan complex plays an important structural role by linking the cytoskeletal protein dystrophin to laminin in the extracellular matrix. Mutations that affect any of the proteins involved in this structural axis lead to myofiber degeneration and are associated with muscular dystrophies and congenital myopathies. Because loss of dystrophin in Duchenne muscular dystrophy (DMD) leads to an almost complete loss of dystroglycan complexes at the myofiber membrane, it is generally assumed that the vast majority of dystroglycan complexes within skeletal muscle fibers interact with dystrophin. The residual dystroglycan present in dystrophin-deficient muscle is thought to be preserved by utrophin, a structural homolog of dystrophin that is up-regulated in dystrophic muscles. However, we found that dystroglycan complexes are still present at the myofiber membrane in the absence of both dystrophin and utrophin. Our data show that only a minority of dystroglycan complexes associate with dystrophin in wild type muscle. Furthermore, we provide evidence for at least three separate pools of dystroglycan complexes within myofibers that differ in composition and are differentially affected by loss of dystrophin. Our findings indicate a more complex role of dystroglycan in muscle than currently recognized and may help explain differences in disease pathology and severity among myopathies linked to mutations in DAPC members.